Synthesis, functionalization and coordination chemistry of dibenzotetraaza[14]annulenes - Abdul, Qaiyum Ramle; Tiekink, Edward R. T. *; Wan, Jefrey Basirun (Elsevier, 2022)
This comprehensive review summarizes recent advances in the synthesis and coordination chemistry of dibenzotetraaza[14]annulenes (DBTAAs) reported between 2010 and 2021. Owing to the smaller N4 donor cavity compared to that of the porphyrin core, it is not surprising that DBTAA offers versatile and unique coordination modes towards metal ions. The structural modification of the DBTAA core allows for the fine-tuning of their spectroscopic properties. DBTAA and derivatives have been utilized across a wide range of research disciplines such as in electronic devices and biological assays. The feasible preparation of ligands and their metal complexes suggests DBTAAs as potential alternatives to porphyrins.